THE EFFECT OF USING GRAPHIC ORGANIZERS AND ESTAFET WRITING IN TEACHING WRITING AT THE ELEVENTH GRADE STUDENTS OF SMAN 20 KABUPATEN TANGERANG IN THE ACADEMIC YEAR 2018/2019 - Nensi Arfika Dewi; Hiqma Nur Agustina; Nirna Nirmala (JIPIS, 2019)
AbstractThe aims of this research are to find out the significant effect of using graphic organizers on improving students writing ability, to find out the significant effect of using estafet writing on improving students writing ability, and to find out that graphic organizers has significant effect than estafet writing on improving students writing ability in teaching writing. The population of this research was the eleventh grade students at SMAN 20 Kabupaten Tangerang. The sample are 60 students of XI IPS 3 and XI IPS 4. This research used quasi experimental group - non-equivalent control group design. The result of this research are: (1) The mean of the students’ score in teaching writing that was taught by using graphic organizers was 83.87 higher than before treatment. (2) The mean of the students’ score in teaching writing that was taught by using estafet writing was 78.53 higher than before treatment. (3) The result showed that graphic organizers technique has more significant effect than estafet writing technique. Therefore, graphic organizers is recommended for senior high school.Keywords: estafet writing, graphic organizers, writing ability AbstrakTujuan dari penelitian ini adalah untuk menemukan pengaruh dari penggunaan graphic organizers terhadap peningkatan kemampuan menulis siswa, untuk menemukan pengaruh penggunaan menulis berantai terhadap peningkatan kemampuan menulis siswa, dan untuk membuktikan bahwa graphic organizers memiliki pengaruh yang lebih signifikan dibandingkan dengan menulis berantai terhadap peningkatan kemampuan menulis siswa dalam pengajaran menulis. Populasi penelitian ini adalah siswa kelas sebelas SMAN 20 Kabupaten Tangerang. Sampel penelitian sebanyak 60 siswa XI IPS 3 dan XI IPS 4. Penelitian ini menggunakan kelompok quasi experimental – non – equivalent grup kontrol. Hasil dari penelitian ini adalah: (1) mean dari nilai siswa dalam pengajaran menulis yang diajarkan dengan menggunakan graphic designers adalah 83,8 lebih tinggi dari sebelum diberikan tindakan. (2) mean dari nilai siswa dalam pengajaran menulis yang diajarkan dengan menggunakan menulis berantai adalah 78,53 lebih tinggi dari sebelum diberikan tindakan. (3) hasil penelitian menunjukan bahwa teknik graphic organizers memiliki pengaruh yang lebih signifikan dibandingkan dengan teknik menulis berantai. Oleh karena itu, graphic organizers direkomendasikan untuk sekolah menengah atas.Kata kunci: graphic organizers, kemampuan menulis, menulis berantai.